An instrument to measure individuals’ research agenda setting: the multi-dimensional research agendas inventory - Horta, H. (2016)
This study developed the Multi-Dimensional Research Agendas Inventory to measure the key factors associated with the process of research agenda setting. Research agendas reflect the preferences, strategies, influences and goals that guide researchers' decisions to investigate specific topics. The results of exploratory and confirmatory factor analyses indicated that the instrument has eight distinct dimensions: Scientific Ambition, Convergence, Divergence, Discovery, Conservative, Tolerance for Low Funding, Mentor Influence and Collaboration. The model underlying the instrument exhibited a very good fit [X-2/df = 1.710; CFI = 0.961; PCFI = 0.791; RMSEA = 0.035; P(rmsea <= 0.05) < 0.001], and the instrument itself was found to have excellent measuring properties (in terms of validity, reliability and sensitivity). Potential interpretations of the instrument and its implications for research and practice are also discussed in this article.